Influence of pretreatment of piperazine ferulate on pharmacokinetic parameters of methotrexate in methotrexate-induced renal injury model rats by HPLC-MS - Huiyan Shi; Chenzhi Hou; Liqiang Gu; Zhe Wei; Hang Xing; Meiyu Zhang; Shixiao Wang; Longshan Zhao; Kaishun Bi; Xiaohui Chen (Elsevier, 2017)
The present study was designed to investigate the influence of the pretreatment of piperazine ferulate on pharmacokinetic parameters of methotrexate in methotrexate-induced renal injury rats. A simple and efficient high performance liquid chromatography coupled with mass spectrometry (HPLC-MS) method was developed to determine methotrexate in rat plasma. Methotrexate and syringic acid (internal standard) were extracted from rat plasma samples by protein precipitation with acetonitrile. The analysis was performed on a CAPCELL PAK C18 column (150 mm × 4.6 mm, 5 µm) with acetonitrile and 5 mmol/l ammonium acetate aqueous (10:90, v/v). The linear range was 5.0 × 10−2 to 100.0 µg/ml for methotrexate. Other parameters were all within the acceptance criteria. The validated method was successfully applied the pharmacokinetic study of methotrexate between two methotrexate treated groups (with and without the pretreatment of piperazine ferulate). Compared with the methotrexate treated alone group, the pharmacokinetic parameters in the methotrexate with the pretreatment of piperazine ferulate group showed significantly lower MRT(0-t), MRT(0-∞) and T1/2. Results suggested that methotrexate can be rapidly eliminated, cleared or metabolized in rat blood, which might be related to the pretreatment of piperazine ferulate. The method provided deeper insights into rational clinical use of methotrexate with the pretreatment of piperazine ferulate on cancer patients with renal dysfunction.